How do practitioners manage decision knowledge during continuous software engineering? - Kleebaum, Anja; Paech, Barbara (Proceedings SEKE 2019, 2019)
We report on results from an interview study with 24 practitioners from 17 companies on how decision knowledge is managed during CSE.